Effects of biochar from algae (Sargassum spp.) on the fertility of two chlordecone contaminated West Indies soil - Perrine Stephan; Pierre Leglize; Loïc Garcia; Lucas Charrois; Paméla Hartmeyer; Aude Fauvet; Séverine Piutti (PLoS ONE, 2025)
The unique properties of biochar (BC) have led to its increasing use as a soil management tool that improves soil fertility and enables pollutant sequestration. In the French West Indies, BC offers a potential solution for mitigating chlordecone (CLD) contamination. This study aims to comprehensively assess the impact of a Sargassum -derived BC (BCS), previously validated to sequester CLD, on soil fertility in the region. A one-year incubation experiment was conducted using two Caribbean soils (Andosol and Nitisol), testing amendments with BCS and activated carbon DARCO® (ACD) at 2% w/w. Fourteen indicators of chemical, biological, and physical fertility and CLD environmental availability were measured throughout the study. The results revealed that the carbonaceous amendments significantly affected soil fertility, in terms of soil and matrix properties. BCS had no effect on physical fertility but increased the availability of sodium (by a factor of 2–4 in both soils) and magnesium (by a factor of 1.5 in Andosol). BCS did not alter the activities of enzymes involved in the carbon cycle, although the activity of arylsulfatase in Andosol increased by 60% in the short and medium-term. However, BCS had a negative effect on leucine-aminopeptidase activity, raising concerns about its potential influence on the nitrogen cycle in soils.